Settlement of Inheritance of Customary Law Perspectives in Tapa District, Bone Bolango Regency, Gorontalo Province - Herno Dalali; Ajub Ishak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
This article discusses the settlement of inheritance to the people of Tapa District perspective of customary law. This research is a field study with data collection methods in the form of observations, interviews and documentation. The collected data were processed and analyzed qualitatively. The results show that: First, the settlement of the heirs to the people of Tapa District is divided into three, namely (1) deliberation negotiations between the two parties; (2) mediation by the District; and (3) apply to the Religious Court; Second: the factors of settlement in the Tapa District community, namely cultural and social factors, educational and economic factors.